Political Corruption and Political Clientelism in Riau Province in 1998-2015 - Doni Hendrik; Mudiyati Rahmatunnisa; Caroline Paskarina; Nandang Alamsah D (International Journal of Social Service and Research, 2023)
This research was motivated by the phenomenon of high cases of corruption of regional heads in Riau province, the strong clientalism relationship and the lack of research on relations (linking) that links corruption with political clientalism with the perspective of political actors and actors themselves. This background has raised a research question, namely "How is the relationship (linking) of political corruption with political clientalism in Riau province in 2004-2015. With a qualitative approach and data collection through in-depth interviews, secondary data collection (documentary). This research has found research findings including; First. There is a close linking and relationship between clientalism and clientalism networks with the corrupt behavior of regional heads in Riau province. Second. Clientelism relationships and networks deliberately built by regional heads during the process of winning regional elections and after regional elections have resulted in the emergence of relationships patterned with elements of cultural aspects of "reciprocity and service" values between actors, brokers and clients' networks of candidates in the regions. In addition to campaign and party costs, clientelism relations between these figures also increase political financing for regional head candidates in Riau. Third. The clientelism network and political brokers used by regional heads in the winning and post-winning processes include; Regional elites, religious leaders, ethnic leaders, leaders of mass and youth organizations, bureaucratic officials, and business networks, where lately the political behavior of these political actors shows an increasingly materialistic and transactional tendency. This has the effect of encouraging/stimulating corruptive behavior among regional heads in Riau province, even corruptive behavior among brokers/actors of the clientalism network itself. Fourth. The existence of relations and influence of local and national entrepreneurs ("political cukong-cukong") in Riau as well as a network of clientelism of a national nature that strongly influences the election process and political processes in Riau.Fifth. The discovery of a form of "bureaucratic" clientalism in the process of winning regional heads who also involved corrupt behavior in Riau province.Sixth. The factor of Riau Province's high natural resource wealth has resulted in high political competition and economic resources are so "hard" among economic and political elites, so that political competition and relations tend to be transactional and pragmatic among the elite and Riau society itself.Seventh. There are still characteristics and values of Malay culture which are still partly feudal in the daily life of people in villages / regions, so that unconsciously "construct" a character of "Nrimo" / Pasrah" among ordinary people, so that it tends to be "not independence / not critical" to the ruler / patron so that the characteristics have made Riau a "fertile" area for regional heads to carry out corruptive actions.